Copeptin in Patients with Pregnancy-Induced Hypertension - Marek, Agnieszka (Int J Environ Res Public Health, 2021)
Pregnancy-induced hypertension (PIH) occurs in 6–8% of pregnancies, and increases the risk of many severe obstetric complications. The etiology of PIH has not been fully explained, and hence, treatment is only palliative in nature, and prevention is not fully effective. It has been proposed that PIH development is influenced by the arginine vasopressin pathway, whose surrogate biomarker is copeptin. The aim of this study is a prospective assessment of the relationship between the level of copeptin in pregnant women and the occurrence of PIH, and to identify its usefulness in predicting complications. The study involved a group of 21 pregnant women who developed PIH and 37 women with uncomplicated pregnancies as a control group. Blood samples were collected at the three trimesters of gestation (<13 HBD, between 13 and 26 and >26 HBD) and then frozen. Copeptin levels [pg/mL] were measured in serum samples obtained in the first, second and third trimesters of gestation from women in the PIH and control groups. The concentration of copeptin in the second and third trimesters of pregnancy was statistically significantly higher in the PIH group (p < 0.05). For copeptin determined in the first trimester, which could be used to screen for PIH, the area under the ROC curve was 0.650. The highest risk of PIH occurred in patients with high concentrations of copeptin in the first trimester of pregnancy and obesity OR = 5.5 (95% CI 1.0–31.3). The risk of PIH was augmented in patients with high levels of copeptin and an abnormal Doppler result of the uterine arteries OR = 28.4 (95% CI 5.3–152). In conclusion, copeptin levels were found to be elevated in pregnant women before the diagnosis of PIH; however, copeptin should not be used as a stand-alone marker. The combination of copeptin concentration with the other risk factors (diabetes, maternal age and preeclampsia in previous pregnancy) did not improve the diagnostic values of the use of copeptin in the PIH risk assessment, but the combination of copeptin concentration with BMI may be useful in clinical practice. Measurement of copeptin together with a Doppler examination of uterine arteries in the first trimester of pregnancy may be a useful marker in predicting the development of PIH.